Using CRISPR/Cas9 genome editing in human iPSCs for deciphering the pathogenicity of a novel CCM1 transcription start site deletion - Pilz, Robin A.; Skowronek, Dariush; Hamed, Motaz; Weise, Anja; Mangold, Elisabeth; Radbruch, Alexander; Pietsch, Torsten; Felbor, Ute; Rath, Matthias (Frontiers in Molecular Biosciences, 2022)
Cerebral cavernous malformations are clusters of aberrant vessels that can lead to severe neurological complications. Pathogenic loss-of-function variants in the CCM1, CCM2, or CCM3 gene are associated with the autosomal dominant form of the disease. While interpretation of variants in protein-coding regions of the genes is relatively straightforward, functional analyses are often required to evaluate the impact of non-coding variants. Because of multiple alternatively spliced transcripts and different transcription start points, interpretation of variants in the 5' untranslated and upstream regions of CCM1 is particularly challenging. Here, we identified a novel deletion of the non-coding exon 1 of CCM1 in a proband with multiple CCMs which was initially classified as a variant of unknown clinical significance. Using CRISPR/Cas9 genome editing in human iPSCs, we show that the deletion leads to loss of CCM1 protein and deregulation of KLF2, THBS1, NOS3, and HEY2 expression in iPSC-derived endothelial cells. Based on these results, the variant could be reclassified as likely pathogenic. Taken together, variants in regulatory regions need to be considered in genetic CCM analyses. Our study also demonstrates that modeling variants of unknown clinical significance in an iPSC-based system can help to come to a final diagnosis.